BUSINESS INCUBATORS AS ENABLERS TO INNOVATION CAPABILITIES OF MSMEs: AN EMPIRICAL EVIDENCE FROM INDONESIA - Faisol, Faisol; Nurdiwaty, Diah; Widiawati, Hestin Sri; Winarko, Sigit Puji (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Business incubators are seen as crucial enablers of innovation, offering mentoring and other support to the budding entrepreneurs and enterprises. Numerous investments have been made by the Governments and other agencies to support the growth of business incubators, including those in the infrastructure, finance, human resources and communication technologies. Using cross-section data from 156 representatives of MSMES in the City of Kediri (East Java Province of Indonesia), this study examines how business incubator capability is perceived to affect the innovation performance of regional MSMEs. Data has been analyzed using Structural Equation Modeling - Partial Least Squares techniques. Service Capacity, Financial Strength and Incubation Capacity has been identified as three important characteristics of the business incubators to support the innovation capability of MSMEs. Additionally, this study found that communication infrastructure in business incubators plays a significant moderating role to influence the innovation performance of MSMEs being incubated. In order to assist the growth of domestic technology entrepreneurs and innovation performance, this study supports the idea that developing economies should prioritize free knowledge transfer platforms through the over business incubators.